PEMAKNAAN MASYARAKAT BELITUNG TERHADAP MARGINALISASI KELOMPOK DAN MOTIVASI DALAM FILM LASKAR PELANGI - Putri Ramadhini; Sri Budi Lestari; Wiwid Noor Rakhmad; Triyono Lukmantoro (Interaksi Online, 2015)
Phenomenal movie titled Laskar Pelangi represent group discrepancy occur in Belitong. Interpretation of Belitong’s citizen toward group marginalization and motivation that happen in Belitong potrayed in Laskar Pelangi to be background of this research. The problem that arises is movie has many multiple interpretations message that could be interpreted by audience in asymmetric way. Audience within Belitong Island have their own mindset to interpret Laskar Pelangi, accompanied their straight experience because the movie has background as it main story in Belitung. The purpose of this research to discribe the interpretation of Belitong’s citizens about marginalization symptom that newcomer group did toward local group, and motivation as represented in Laskar Pelangi movie. This reserarch uses theory of social stratifications, theory of active audience, and theory of audience interpretation with reception analyze methods. Object of research is Belitong’s local citizens that watched Laskar Pelangi movie. The result is show audience capability to identify group marginalization potrayed in many scene such as the comparison between students PN Timah primary school with Muhammadiyah primary school. Discrepancy also seen from the difference of look, tools and infrastucture of school, activities during holiday and their job. Boundary areas between groups be marked on guardrail with disallowance to enter specific area. Informants have different interpretation and interpret movie based on mindset that being affected b y their own background. Based on the decoding-encoding audience theory of Stuart Hall, informants grouped in Dominant-Hegemonic Position, Negotiated Position and Oppositional Position.Informant at Dominant-Hegemonic position accept the meaning as it contained in the film about group marginalization and motivation recognized by the informant indeed found in the real life. Informant at Negotiated position generally accept the meaning as it defined and signed but deny some inappropriate aspect because being represented excessively and unsuitable according Belitongs conditions are better than before. Informant at Opppositional position measure scenes in the film were too excessive and only intended to make the story being more attractive, even considered disfigure the condition of Belitong’s society that couldn’t found in the real life.